A Comparison of Pd0 Nanoparticles and Pd2+ Modified Bi2O2CO3 for Visible Light-Driven Photocatalysis. (1st January 2018) - Meng, Xiangchao; Li, Zizhen; Yun, Nan; Zhang, Zisheng
Abstract : As two effective approaches to increase the visible light-absorption capacities of photocatalysts, ion doping and metallic nanoparticles loading are compared in this work. Palladium was selected to modify Bi2 O2 CO3 . Compared to dispersing palladium nanoparticles on the photocatalyst surface, it was more effective for the method of doping with palladium to shift the energy level within the bandgap of Bi2 O2 CO3 in improving its photocatalytic activity under visible light. This might be because doping with Pd 2+ narrows the band gap of Bi2 O2 CO3 so as to increase the absorption capacity of visible light photons. Pd nanoparticles on the other hand can absorb photons to produce electrons which are then utilized by Bi2 O2 CO3 for photocatalytic reactions. Different mechanisms resulted in significant differences, and this work provides solid evidence that ion doping may be a more effective method to improve the photocatalytic activity of Bi2 O2 CO3 .